2021
DOI: 10.3390/vaccines9020130
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Obesity and Being Overweight on the Immunogenicity to Live Attenuated Hepatitis A Vaccine in Children and Young Adults

Abstract: Prior results investigating a correlation between obesity and hepatitis A virus (HAV) vaccine response have been inconclusive, with limited data involving live attenuated HAV vaccines. The aim of this study is to evaluate the effect of overweight and obesity on the response to live attenuated HAV vaccine in children and young adults. This prospective cohort study was conducted in Thailand with subjects ranging in age from seven to twenty-five years. The subjects were administered 0.5 mL of MEVAC™-A and tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Frequent eating habits might be one possible factor that increased their exposure to natural HAV infections. A previous study conducted in Thailand also reported that truncal obesity was a strong associated factor of a better immune response to single-dose live-attenuated HAV vaccine 27 . To date, the plausible mechanisms of the association between overweight/obesity and strong immune response to HAV infection or vaccination are not clearly understood 28 .…”
Section: Discussionmentioning
confidence: 80%
“…Frequent eating habits might be one possible factor that increased their exposure to natural HAV infections. A previous study conducted in Thailand also reported that truncal obesity was a strong associated factor of a better immune response to single-dose live-attenuated HAV vaccine 27 . To date, the plausible mechanisms of the association between overweight/obesity and strong immune response to HAV infection or vaccination are not clearly understood 28 .…”
Section: Discussionmentioning
confidence: 80%
“…Specifically, poor antibody responses have been reported in obese individuals upon tetanus ( 70 ), influenza ( 66 , 71 ) or inactivated SARS-CoV-2 ( 72 ) vaccinations. In contrast, other vaccination regimes, such as live-attenuated hepatitis A, have been shown to be equally effective in both obese and lean individuals, suggesting that other factors may be at play ( 73 ). Furthermore, several studies have observed lower antibody titres upon influenza vaccination in obese individuals, and this defect is typically mirrored by decreased protection from influenza-related complications compared with non-obese individuals ( 74 , 75 ).…”
Section: Systemic Metabolism and Vaccine Responsesmentioning
confidence: 99%